Impaired holistic processing of left-right composite faces in congenital prosopagnosia - Liu, Tina T.; Behrmann, Marlene (Frontiers in Human Neuroscience, 2014)
Congenital prosopagnosia (CP) refers to a lifelong impairment in face processing despite normal visual and intellectual skills. Many studies have suggested that the key underlying deficit in CP is one of a failure to engage holistic processing. Moreover, there has been some suggestion that, in normal observers, there may be greater involvement of the right than left hemisphere in holistic processing. To examine the proposed deficit in holistic processing and its potential hemispheric atypicality in CP, we compared the performance of 8 CP individuals with both matched controls and a large group of non-matched controls on a novel, vertical composite task. In this task, participants judged whether a cued half of a face (either left or right half) is the same or different at study and test, and the two face halves can be either aligned or misaligned. The standard index of holistic processing is one in which the unattended face half influences performance on the cued half and this influence is greater in the aligned than in the misaligned condition. Relative to controls, the CP participants, both at a group and at an individual level, did not show holistic processing in the vertical composite task. There was also no difference in performance as a function of hemifield of the cued face half in the CP individuals, and this was true in the control participants, as well. The findings clearly confirm the deficit in holistic processing in CP and reveal the useful application of this novel experimental paradigm to this population and potentially to others as well.